The Agricultural Digital Divide: Impact of Internet Penetration on Mechanization Adoption and Labor Productivity in Rural Areas - A. St. Fatmawaty; Amruddin Amruddin; Erina Riak Asie (Agriculture Journal, 2026)
The agricultural sector faces a structural divide between traditional practices and data-driven digitalization. This research investigates the influence of rural internet penetration on the adoption of modern agricultural machinery and its impact on labor productivity in Indonesia. Utilizing a quantitative framework, the study synthesizes official secondary data from national labor, digital development, and agricultural databases covering 38 provinces. Results demonstrate a significant positive correlation, where high-connectivity regions exhibit a 63.46% higher productivity index compared to digitally isolated areas. Path analysis reveals that internet penetration serves as a critical enabler, where gains in labor efficiency are predominantly mediated by the adoption of physical mechanization. However, low digital literacy in Eastern Indonesia remains a structural constraint. The study concludes that while rural internet penetration plays an important role in accelerating mechanization adoption, its effectiveness in improving agricultural productivity is highly dependent on digital literacy and the integration of digital infrastructure with mechanization practices.